A NOVEL STABILITY INDICATING RP-HPLC METHOD DEVELOPMENT AND VALIDATION FOR THE QUANTIFICATION OF ARIPIPRAZOLE IN PURE AND ITS PHARMACEUTICAL FORMULATION - K, Vijayabharathi; Shaik Muneer; Kb, Chandra Sekhar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study was aimed to develop a novel, selective, and sensitive reverse phase high performance liquid chromatography method for the detection and quantification of aripiprazole in pure form as well as in its pharmaceutical formulation. Methods: The chromatography was carried out on C18 Phenomenex Luna (250 × 4.6 mm × 5 μm) column using a mobile phase of 0.1% v/v orthophosphoric acid (pH 3.0), acetonitrile and methanol in the ratio of 40:50:10 (% v/v). The isocratic elution program was adjusted to 1.0 ml/minutes flow rate with 20 μl injection volume. The eluted components were monitored at 254 nm. The ambient column oven temperature was maintained. Results: The developed method was validated statistically with respect to linearity, range, precision, accuracy, specificity, robustness, ruggedness, detection and quantification limits and also subjected to various stress conditions such as acidic and alkaline hydrolysis, oxidation, photolysis, and thermal degradation. The method showed linearity across the concentration range of 10.0-60 μg/ml. Conclusion: The developed method is specific, precise, accurate, robust and stability indicating which can be successfully applied for routine analysis, quality control analysis and also suitable for stability analysis of assay of aripiprazole in pure form and its formulation as per the regulatory requirements.